2013
DOI: 10.1155/2013/834605
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Fibrodysplasia Ossificans Progressiva in an Egyptian Infant with c.617G > A Mutation inACVR1Gene: A Case Report and Review of Literature

Abstract: Fibrodysplasia ossificans progressiva (FOP) is an autosomal dominant severe musculoskeletal disease characterized by extensive new bone formation within soft connective tissues and unique skeletal malformations of the big toes which represent a birth hallmark for the disease. Most of the isolated classic cases of FOP showed heterozygous mutation in the ACVR1 gene on chromosome 2q23 that encodes a bone morphogenetic protein BMP (ALK2). The most common mutation is (c.617G > A) leading to the amino acid substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“… 15 , 16 Genetic analysis of FOP patients has identified gain-of-function mutations in ALK2 , including c.617G>A (p.R206H), c.619C>G (p.Q207E), c.1067G>A (p.G356D), c.982G> T(p.G328W), c.983G> A(p.G328E), c.982G>A (p.G328R), c.774G>C/c.774G>T (P.R258S), c.1124G>C (p.R375P), c.587T>C (p.L196P), c.590–592delCTT (p.P197_F198delinsL), and c.605G>T (p.R202I), among which R206H is the most common mutation and can be found in ~90% of FOP patients. 17–31 The classic, constitutively active ALK2 receptor containing the artificial Q207D mutation or the R206H mutation recaptures the FOP condition in transgenic animal models. 32 , 33 Further evaluation of these FOP mutations revealed that the ectopic expression of ALK2 increased Smad-dependent BMP signaling activity, which potentially occurs for both osteogenic and chondrogenic differentiation of myoblasts, thus forming heterotopic bone through an endochondral bone formation process.…”
Section: Biological Functions Of Alk2 In Bone Formationmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 16 Genetic analysis of FOP patients has identified gain-of-function mutations in ALK2 , including c.617G>A (p.R206H), c.619C>G (p.Q207E), c.1067G>A (p.G356D), c.982G> T(p.G328W), c.983G> A(p.G328E), c.982G>A (p.G328R), c.774G>C/c.774G>T (P.R258S), c.1124G>C (p.R375P), c.587T>C (p.L196P), c.590–592delCTT (p.P197_F198delinsL), and c.605G>T (p.R202I), among which R206H is the most common mutation and can be found in ~90% of FOP patients. 17–31 The classic, constitutively active ALK2 receptor containing the artificial Q207D mutation or the R206H mutation recaptures the FOP condition in transgenic animal models. 32 , 33 Further evaluation of these FOP mutations revealed that the ectopic expression of ALK2 increased Smad-dependent BMP signaling activity, which potentially occurs for both osteogenic and chondrogenic differentiation of myoblasts, thus forming heterotopic bone through an endochondral bone formation process.…”
Section: Biological Functions Of Alk2 In Bone Formationmentioning
confidence: 99%
“… 32 , 33 Further evaluation of these FOP mutations revealed that the ectopic expression of ALK2 increased Smad-dependent BMP signaling activity, which potentially occurs for both osteogenic and chondrogenic differentiation of myoblasts, thus forming heterotopic bone through an endochondral bone formation process. 21 , 32 , 34–39 In addition, inhibiting the activation of BMP signaling effectors Smad1/5/8 in tissues that constitutively express ALK2 resulted in a reduction of the ectopic ossification and functional impairment. 32 The stable in vitro transfection of the Alk2 R206H mutation in C2C12 cells (mouse myoblasts) increased the levels of both osteogenic markers ( osterix ( Osx ), alkaline phosphatase ( Alp )) and chondrogenic markers ( type II collagen ( Col2 ), type X collagen ( Col10 )).…”
Section: Biological Functions Of Alk2 In Bone Formationmentioning
confidence: 99%
“…Some of the patients show sparse hair, thin facial skin and missing eyebrows, leading to a possibly recognizable craniofacial aspect in FOP patients [Kaplan et al, 2009;Stefanova et al, 2012;Al-Haggar et al, 2013]. Most of the patients show ulnar deviation of the great toes ( fig.…”
Section: Patients With the Classical Mutation C617g>a (Pr206h) In Ementioning
confidence: 99%
“…Patient #1 has a more advanced disease than patient #2, possibly due to the fact that he is older. After comparing the characteristics of the two patients with those described by Kaplan et al ,7 Zhang et al ,8 Stefanova et al ,9 Carvalho et al ,10 Nakajima et al 11 and Al-Haggar et al ,12 many similarities were found, as seen in table 1;3 nevertheless, although the two patients discussed present a ‘classical’ FOP phenotype and genotype, they present mental retardation, which is an atypical FOP clinical feature.…”
Section: Discussionmentioning
confidence: 59%